PENGARUH METODE DISKUSI BERBANTUAN LEMBAR AKTIVITAS SISWA (LAS) TERHADAP PEMAHAMAN KONSEP SISWA PADA MATERI OPTIKA GEOMETRIS KELAS X SMA - Muhammad Yafi Syaifuddin (Jurnal Penelitian Pembelajaran Fisika, 2015)
This study was aimed to determine the effect of discussion method with student activity sheet toward the students' understanding of the concept. The design of the study is quasi experiment in the form of nonequivalent control group. This design is similar to the pretest-posttest control group design. This study was conducted in SMA Kesatrian 1 Semarang on 25 April to 6 May 2015 with a population of an entire class X MIA SMA Kesatrian 1 Semarang. The sample consisted of two classes taken with random cluster sampling technique that is class X MIA 5 as experimental class and the class X MIA 6 as the control class. The data collecting technique were documentation and written test method (pretest and posttest). According to the data analysis of pretest, it was obtained the means of the pretest score of experimental class that was 22,87 and the control class was 17,33. And after the learning given, posttest was held in both classes, the result for the experimental class was 84.53 and the control class is 74.53. Testing the hypothesis with a significance level of 0.05 was obtained  = 4,569 and  = 1,671. These results indicate that  >  (4.569 > 1.671). It can be concluded that  is rejected. Thus, it can be concluded that the discussion method with student activity sheet provides positive impacts toward the students’ concept understanding.